Effect of Immediate vs Delayed Pushing on Rates of Spontaneous Vaginal Delivery Among Nulliparous Women Receiving Neuraxial Analgesia: A Randomized Clinical Trial. Issue 3 (March 2019) - Cahill, Alison G.; Srinivas, Sindhu K.; Tita, Alan T. N.; Caughey, Aaron B.; Richter, Holly E.; Gregory, W. Thomas; Liu, Jingxia; Woolfolk, Candice; Weinstein, David L.; Mathur, Amit M.; Macones, George A.; Tuuli, Methodius G.
Abstract : (Abstracted from JAMA 2018;320(14):1444–1454) Despite the frequency of childbirth, many aspects of labor management lack an evidence-based approach. The second stage of labor, defined as the interval from complete cervical dilation through delivery of the fetus, is the most physiologically demanding period of labor for both the mother and the fetus.